2015
DOI: 10.1177/0300985815593123
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Pathology and Pathogens in Wild Urban Rats (Rattus norvegicus and Rattus rattus)

Abstract: Norway (Rattus norvegicus) and black rats (Rattus rattus) are common peridomestic species, yet little is known about wild rat ecology, including their natural diseases. We describe gross and histological lesions in the respiratory tract of a sample of 711 wild urban rats. A subset was examined for 19 distinct categories of histological lesions in the respiratory tract. Testing for known respiratory pathogens included serology and polymerase chain reaction (PCR) of lung samples. Grossly evident lesions were rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 32 publications
1
27
1
Order By: Relevance
“…Based on univariable analysis, the following variables were significantly associated with L. interrogans : Capillaria hepatica in the liver, bite wounds, other macroscopic lesion(s), cardiomyopathy, non‐glandular stomach lesions, thyroid goitre, iBALT, tracheitis, urinary crystals and nematode in any organ (Table ). Tracheitis and iBALT in the lungs are related variables since both lesions are attributable to bacterial respiratory infections (cilia‐associated respiratory bacillus and/or Mycoplasma pulmonis (Rothenburger, Himsworth, Clifford, et al, ). Similarly, data for C. hepatic in the liver are captured by nematode in any organ variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on univariable analysis, the following variables were significantly associated with L. interrogans : Capillaria hepatica in the liver, bite wounds, other macroscopic lesion(s), cardiomyopathy, non‐glandular stomach lesions, thyroid goitre, iBALT, tracheitis, urinary crystals and nematode in any organ (Table ). Tracheitis and iBALT in the lungs are related variables since both lesions are attributable to bacterial respiratory infections (cilia‐associated respiratory bacillus and/or Mycoplasma pulmonis (Rothenburger, Himsworth, Clifford, et al, ). Similarly, data for C. hepatic in the liver are captured by nematode in any organ variable.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiomyopathy is a known cause of mortality in laboratory rats and is suspected to similarly impact wild rat health (Keenan, Soper, Smith, Ballam, & Clark, ; Rothenburger, Himsworth, Treuting, & Leighton, ). Tracheitis, associated with respiratory pathogens (CAR bacillus and M. pulmonis ), is indicative of respiratory disease (Rothenburger, Himsworth, Clifford, et al, ). Bite wounds ranged in severity but were often infected (Himsworth, Zabek, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Migration of leukocytes to tissues is a normal response to a variety of tissue insults, primarily microbial penetration, which may compromise cell/tissue integrity and is necessary for immune surveillance and effector functions (Friedl & Weigelin 2008;Nourshargh & Alon 2014). Indeed, wild rats harbor a variety of pathogens (Easterbrook et al 2007;Meerburg et al 2009;Rothenburger et al 2015;Pépin et al 2016) and our preliminary microbiological survey of lungs, liver and kidneys showed the presence of several pathogenic bacteria as well. Although immune-based activities in tissues can be taken as related to microbial infection, the influence of environmental toxicants shall not be excluded.…”
Section: Discussionmentioning
confidence: 83%
“…This agent acts synergistically with other respiratory pathogens including Mycoplasma pulmonis, Sendai virus, coronavirus, Streptococcus pneumoniae, Corynebacterium kutscheri, Bordetella bronchiseptica, Klebsiella pneumoniae, or Pasteurella spp. Lesions include suppurative to mucopurulent bronchopneumonia, perivascular and bronchiolar lymphoid hyperplasia, rhinitis and lymphoplasmacytic tracheitis in free-ranging, pet and laboratory rats Rothenburger et al, 2015b). Coinfection of CAR bacillus and mycoplasmas has been reported in rats and spinifex hopping mice with pneumonia (Mackie et al, 2001).…”
Section: Nonzoonotic Bacteriamentioning
confidence: 99%
“…Histologic lesions include peribronchial lymphoid cuffing with BALT hyperplasia; neutrophilic bronchopneumonia; type II pneumocyte hyperplasia of alveolar epithelium; and emphysema; bronchiectasis is a characteristic finding. Histology alone cannot differentiate M. pulmonis and CAR bacillus respiratory infections (Rothenburger et al, 2015b). Other lesions associated with M. pulmonis include endometritis, salpingitis, and perioophoritis.…”
Section: Nonzoonotic Bacteriamentioning
confidence: 99%